(untitled) - Michael J Wallace (Cambridge, New York, 1980)
The book covers the skills which relate directly to the needs of most students: improving reading efficiency; taking notes; preparing for seminars; research techniques; how to organise and present essays; preparing for examinations
Keywords: english - study and teaching